La gestión administrativa y la logística en la gerencia sub Regional de Ucayali Contamana 2023 - Gomez Ruiz, Antony (2024)
The main objective of this research work was to establish the connection between administrative management and logistics in the Sub Regional Management of Ucayali, Contamana 2023. An applied research was carried out, with a descriptive-correlational approach and a design not experimental. The sample was made up of 94 employees, to whom a questionnaire was applied as an instrument to measure the variables of interest. Among the results obtained through the respective programs, it was found that 35% perceive administrative management as regular, since, although management usually has clarity in its mission, vision and institutional objectives, it frequently lacks defined strategies to achieve these objectives, in Sometimes resources are allocated for planned activities, the organizational structure is rarely updated. Likewise, 29% rate the logistics in said entity as regular, since the requirements are not always met with the expected speed; quotes are usually made in accordance with Law 30255. Finally, it was concluded that there is a highly significant positive relationship between the administrative management and logistics (Spearman's rho of 0.741; bilateral sig. of 0.000), likewise administrative management has a significant relationship between the supply programming dimensions (r = 0.684; sig. = 0.000); Acquisition of goods and services (r = 0.746; sig. = 0.000); Storage (r = 0.670; sig. = 0.000); Distribution of assets (r = 0.647; sig. = 0.000).